Karyological investigation of six Achillea L. (Asteraceae) species growing in Turkey - Kiran, Yasar; Turkoglu, Ismail; Kirilmaz, Fatma; Arabaci, Turan; Sahin, Ahmet; Bagci, Eyup (Firenze Univ Press, 2012)
The chromosome number and morphology in six species of the sections Babounya (DC.) O. Hoffm. and Achillea of the genus Achillea L. (Asteraceae) were investigated using karyological techniques. Sample plants and seeds of A. santolinoides Lag. subsp. wilhelmsii (K. Koch.) Greuter, A. falcata L., A. magnifica Hub. - Mor., A. pannonica Scheele, A. crithmifolia Waldst. & Kit. and A. nobilis L. subsp neilreichii (A. Kern.) Formanek were collected from natural habitats in 2005. The chromosome number found in six species was 2n = 18. All chromosomes had median point (M), median region (m), and submedian (sm) centromers. An increase in asymmetry was not observed in the karyotypes of the species studied. None of the studied species had any B chromosomes.
Keywords: Achillea; Asteraceae; chromosome number; karyotypes; mitosis; Turkey